EDUCATING RILEY COUNTY SENIORS IN BASIC NUTRITION - Sperry, Emily (My University, 2017)
The average age of the population of the United States continues to increase. Older adults are one group of people that are often missed when programs are developed for nutrition. Even though they largely consume food that younger and middle-aged adults do, there are specific things to keep in mind when choosing food for an older adult. There are certain nutrients that they need and others that may cause medical complications if they are consumed in large amounts. The purpose of this project was to develop and present a six-week course in basic nutrition to an older audience with the hopes of educating them on small changes they can make that can lead to a higher quality of life. A pre-assessment and a post-assessment were used to determine if the program had an impact on participants
Keywords: Nutrition; Older Adults; Food Safety; Shopping Tips; Proportions; Labels